Batik Penguatan Identitas Nasional Melalui Pembelajaran Membatik Pada Jurusan Tekstil Di SMK Negeri 6 Pontianak - Anggreni, Adetiya; Zakso, Amrazi; Utami, Tri; Achmadi , Achmadi; Sastra Atmaja, Thomy (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Local culture-based learning plays a strategic role in strengthening students' national identity amidst the challenges of globalization. Batik, as Indonesia's cultural heritage, has the potential to be integrated into vocational learning as a medium for cultural and national education. This research aims to analyze the role of teachers and schools in forming national identity through batik learning, identify supporting and inhibiting factors, and examine the impact of batik learning on the understanding of national identity among Textile major students at SMK Negeri 6 Pontianak. The research uses a descriptive qualitative approach and was conducted from May to June 2025 at SMK Negeri 6 Pontianak, focusing on the 11th grade, Textile major. Research informants included the school principal, the Pancasila and Civic Education teacher, the productive teacher of the Textile major, and five students. Data collection was done through observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, while data validity was ensured through source and technique triangulation. The results show that teachers and schools play an important role in integrating cultural and national values through batik learning. Supporting factors include teacher commitment, school facility support, and student enthusiasm, while inhibiting factors include time constraints and the lack of a written policy. Batik learning has a positive impact on students' understanding of national identity through increased cultural knowledge and national pride.